Answer :

Using splitting middle term, the middle term of the general equation is divided in two such values that:

Product = a.c


For the given equation


= =


And either of their sum or difference = b


=


Thus the two terms are


Sum =


=


=


Product = using


= =






x[x-(2a + b)]-(2a-b)[x-(2a + b)] = 0


[x-(2a-b)][x-(2a + b)] = 0


[x-(2a-b)] = 0 or [x-(2a + b)] = 0


x = (2a-b) or x = (2a + b)


Hence roots of equation are x = (2a - b) or x = (2a + b)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses